EVALUASI PENYUSUNAN ANGGARAN DAN KINERJA KEUANGAN DI KECAMATAN SONDER KABUPATEN MINAHASA - Pangalila, Chelsea; Elim, Inggriani; Walandouw, Stanley Kho (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Budget is a blueprint of the existence of a State and is a future directive. The Local Government Budgeting Process should be a benchmark for achieving the expected performance, so that regional budget planning should be able to clearly describe the performance objectives. With the preparation of a good budget, can be easily obtained information in decision-making. Local governments are responsible for the management of local finances. In the implementation of regional financial management, the regional head holds the general power obliged to carry out in accordance with the Rules that have been determined. In order for the implementation of local financial management carried out in an orderly and obedient to the applicable legislation. The purpose of this research is to know how the process of budget preparation and how the financial performance in Sonder District of Minahasa regency. Data collection method used is qualitative descriptive analysis that is by describing the preparation of budget and financial performance of local government in subdistrict sonder. The results of the research show that the process of Budgeting Process in Sonder District starts from the preparation of the Local Government Work Plan (RKPD), KUA / PPAS up to the Working Budget Plan of Local Government Work Unit (RKA-SKPD) Then presented to the Implementation Document of the Budget of Work Unit of Regional Region (DPA-SKPD). Budgeting and financial performance of local government in Kecamatan Sonder is quite effective. where the budgeting is done using the Planning, Programming, and Budgeting System (PBBS) approach, and the financial performance in the preparation of the budget goes well despite the delay but the implementation is still good and under control. This can be seen from how the process of preparing the budget and strategic plans that are set in the long term.Keywords: Budget Drafting Process, Financial Performance